Mission Strategies of the Evangelical Church of West Africa Among the Maguzawa in Kano and Katsina States, 1954 – 2007 (2013)
The Evangelical Church of West Africa (ECWA) is a church that recorded remarkable proselytising success among the Maguzawa in Kano and Katsina States despite the people‟s resistance to Islam or Christianity. This achievement notwithstanding, little attention has been paid to the history and strategies adopted by the church to Christianise the Maguzawa. This study, therefore, investigated the evangelistic strategies the ECWA deployed in the Maguzawa communities in Kano and Katsina States from 1954-2007, with a view to assessing their impact on the communities. The study was premised on Donald McGavran's People Movement theory which emphasises multi-individual conversion. Data for the study were collected through interviews, church records and questionnaire. Oral interviews were conducted with 80 purposively selected respondents, clergy (40) and the laity (40). Four hundred copies of a questionnaire were randomly administered; out of which 372 were retrieved from 74 Pastors, 36 students of ECWA Theological College, Tofa, and 96 church members in Kano State; and 73 pastors and 93 church members in Katsina State. Qualitative data were subjected to critical and historical analysis, while quantitative data were analysed using percentages. The ECWA adopted seven mission strategies among the Maguzawa. The first was the empowerment of the laity in frontline evangelism, making it possible for the ECWA to reach wider prospective converts between 1954 and 1980. To consolidate the faith of the converts and raise their social level, literacy classes were organised which led to the people‟s social and political mobility from 1954 till date. Third, medical services were introduced as the church‟s response to transmissible diseases, leading to unprecedented improvement in the people‟s health conditions (1954-1990), including awareness about HIV/AIDS (1996 to date). Fourth, to penetrate the social restrictions to Hausa women, Women‟s Fellowship (1954 to date) was organised which increased women participation in grassroots evangelism. Fifth, theological education was introduced in 1970 to professionalise the leadership of the indigenous churches and systematise their church planting strategies. Sixth, to attract new converts, conversion celebrations were introduced in 1977, which consolidated ecumenical ties among the various denominations in Maguzawa communities. Seventh, the church collaborated with Radio Nigeria in 2004 to broadcast the programme, Bangaskiyar Krista to preach to people yet to be reached through personal contact. A total of 86.6% respondents agreed that the empowerment of the laity enhanced the conversion prospects of the ECWA; 93.6% that literacy classes led to a new social order among the Maguzawa; 100% that ECWA medical services complemented government health provisions; 94.6% that women‟s fellowship enhanced women evangelism; 90.9% that theological education broadened the ECWA leadership skills. Also, 95.5% concurred that conversion celebration strengthened the faith of converts; and 85.8% that the radio broadcast provided avenues for mass media evangelism. The seven strategies adopted by the Evangelical Church of West Africa among the Maguzawa, shrunk into evangelistic, educational, medical and media strategies, served as veritable means of Christianising and sensitising the people in social and political terms. The adoption of these strategies by other churches will enhance further proselytisation work in Northern Nigeria